Penguatan Budaya Keselamatan dan Kesehatan di Sekolah Menengah Atas melalui Pencegahan Bullying sebagai Upaya Menciptakan Lingkungan Belajar Sehat Aman Berkelanjutan - Nurwadia Sri Putri Rahmadani; Mas'um, Cicci Chairunisa; Rasmiaji Rasmiaji (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Bullying is a psychosocial hazard that can occur in the school environment and may negatively affect students’ mental health, social interactions, and learning processes. Bullying can take various forms, including physical, verbal, and psychological actions that occur repeatedly and cause victims to experience emotional distress, decreased learning motivation, and feelings of insecurity at school. This Community Service Program (PKM) aimed to increase high school students’ knowledge and awareness regarding the dangers of bullying and its prevention through the principles of Occupational Safety and Health (OSH). The methods used in this activity included delivering educational materials through lectures, conducting question-and-answer sessions to assess students’ initial understanding, and facilitating interactive discussions to encourage active participation. Monitoring and evaluation were also conducted to assess the effectiveness of the activity. The results of the program indicated a significant improvement in students’ understanding and awareness of the forms, impacts, and prevention strategies related to bullying in the school environment. Students also demonstrated a more critical attitude toward bullying behavior and a greater awareness of the importance of creating a safe, healthy, and respectful school environment. The application of an OSH-based approach in bullying prevention is expected to strengthen the safety culture in schools and support the development of a conducive learning environment for all students.